Problemas de segundo orden: hacia una actualización semántica de la crítica inmanente - Martínez, Erika (2018)
The purpose of this article is to crisscross Rahel Jaeggi’s proposal of an immanent critique of forms of life with Robert Brandom’s inferentialist theory. The process of rationalization of a community of speakers’ cultural and conceptual resources developed by Brandom is useful to understand forms of life as solving instances of second-order problems. To this end, I will explain Jaeggi’s notion of forms of life as solving instances of second-order problems, which I will complement with Brandom’s “expressive freedom”. Secondly, I will develop his inferentialist approach, which I will articulate with second-order problems in relation to the explanation of the inferential relations of concepts within a space of reasons. Finally, I will develop the argument in which the opening of a space of reasons may be understood as the place where one can find the germ of the critique that could lead to social transformation.